2021
DOI: 10.1186/s12939-021-01472-9
|View full text |Cite
|
Sign up to set email alerts
|

Symbolic annihilation of Syrian refugees by Turkish news media during the COVID-19 pandemic

Abstract: Background This article presents a discussion about the representation of Syrian refugees in Turkish news media during the COVID-19 pandemic. Media play a critical role during pandemics by affecting values, opinions, public knowledge about stigmatized groups. When media ignore and stereotypically represent a social group, the social value of the group decreases, and their problems are trivialized. Method I analyzed data provided by Media Monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…1 The virus, which was declared by the WHO as a pandemic on March 11, 2020, was born as a deadly disease that has a comprehensive impact on the entire world community today. 2 In line with the previous view, in addition to physical health problems, Covid-19 also has an impact on mental health problems through the emergence of various kinds of stigma or what is known as the Covid stigma. 3 The Covid stigma is a negative view that attaches to individuals due to the influence of a messy social environment due to the Covid-19 outbreak.…”
Section: Introductionmentioning
confidence: 65%
“…1 The virus, which was declared by the WHO as a pandemic on March 11, 2020, was born as a deadly disease that has a comprehensive impact on the entire world community today. 2 In line with the previous view, in addition to physical health problems, Covid-19 also has an impact on mental health problems through the emergence of various kinds of stigma or what is known as the Covid stigma. 3 The Covid stigma is a negative view that attaches to individuals due to the influence of a messy social environment due to the Covid-19 outbreak.…”
Section: Introductionmentioning
confidence: 65%
“…The outbreak of COVID-19 further exacerbated the challenges Syrian refugees faced accessing healthcare in Turkey. Stereotypical representations of Syrian refugees during the pandemic by the local media ignored their specific health challenges [ 73 ], some of which included: loss of income as a result of stay-home directives leading to financial constraints and reducing their capabilities to access medical facilities [ 74 ]; the difficulties refugees had observing social distancing due to overcrowded and unsanitary urban refugee housing [ 75 ]; and the fear of losing their jobs and only source of income meant that many refugees would not report COVID-19 symptoms, thereby increasing the spread within their communities [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted by Fouad et al among Syrian refugees in Lebanon showed that refugees have little knowledge of COVID-19 ( 33 ). Yücel also stated in his research that during the COVID-19 pandemic, Syrian refugees in Turkey are ignored by the media and this issue further aggravates inequalities ( 44 ). In fact, Afghan women were deprived of access to information due to insufficient literacy to study and lack of information resources such as television, etc., and this deprivation made them very vulnerable in the face of COVID-19 because it deprived them of sufficient knowledge and awareness so that in many cases the participants had incomplete and little information about COVID-19 and how to prevent and treat it.…”
Section: Discussionmentioning
confidence: 99%